Effect of IMF By on the Entry of Solar Wind Ions Into the Near‐Earth Tail Lobe: Global Hybrid Simulation and MMS Observation. Issue 9 (29th August 2022) - Wang, Chih‐Ping; Xing, Xiaoyan; Wang, Xueyi; Avanov, Levon A.; Lin, Yu; Strangeway, Robert J.; Wei, H. Y.
Abstract: Global simulations predict that the low‐latitude mantle may be an important pathway for the solar wind entry into the tail magnetosphere close to the current sheet when interplanetary magnetic field (IMF) B y dominates over IMF B z . To evaluate this entry mechanism in the near‐Earth tail ( X ∼ −10–−20 R E ), we investigate the predictions from 3D global hybrid simulations as well as in situ observations by magnetospheric multiscale (MMS) spacecraft. The simulations predict that the low‐latitude mantle plasma can appear in the near‐Earth tail lobe extending inward approximately 5 R E from the flank magnetopause. The low‐latitude mantle plasma appears in the dawnside northern lobe and duskside southern lobe during positive IMF B y, while the opposite asymmetry is seen during negative IMF B y . After a change in the IMF B y direction arriving at the bow shock nose, it takes another ∼15–30 min for the asymmetry to completely reverse to the opposite sense in the near‐Earth tail. We present six MMS events in the tail lobe showing that the existence and absence of the low‐latitude mantle plasma is consistent with the predicted asymmetries. Statistical analysis of 5 years of MMS observations shows that the dependencies of the magnitudes of the lobe densities and tailward field‐aligned flow speeds on the IMF B y directions are consistent with the predicted contributions from the low‐latitude mantle plasma in the expected lobe regions. Key Points: Global hybrid simulations predict that the low‐latitude mantle plasma can form in the near‐Earth lobe controlled by interplanetary magnetic field (IMF) B y Low‐latitude mantle is in dawnside northern lobe and duskside southern lobe for positive IMF B y . The asymmetry reverses for negative IMF B y Statistical analysis of magnetospheric multiscale data supports the simulation predicted dependence of near‐Earth low‐latitude mantle on the IMF B y direction